Plant Roots - Yildirim, Ertan; Turan, Metin; Ekinci, Melek (IntechOpen, 2021)
The root is an organ that generally grows into the soil in developed plants that have adapted to terrestrial life but rarely is found above the ground. The roots have channels to transport nutrients and water to the stem and leaves. Studies on roots will provide opportunities to develop food security and environmental sustainability. This book explains root-soil interactions, ethnobotanical use of roots, secondary metabolite production, and soil resource acquisition from agricultural and ecological perspectives.